Investigation of high-cycle fatigue properties of 3D-printed steel parts - Teo, Timothy Yong Chuen (Nanyang Technological University, 2020)
As additive manufacturing technologies mature and advance over the years, the demand of additive manufacturing has also increased across various industries including the marine industry. High Strength Low Alloy (HSLA) API 5L X65 is a common material used for marine applications due to its superior mechanical properties. Additive manufacturing of API 5L X65 using Laser Engineered Net Shaping (LENS) processes enables more geometrically complex components to be manufactured for the marine industry. However, LENS additive manufacturing processes come with their set of disadvantages. Manufacturing process induced defects such as inclusions, porosity and un-melted particles can be present in such LENS manufactured components affecting their mechanical properties negatively. Hence, this Final Year Project seeks to investigate the high cycle fatigue properties of 3D- printed API 5L X65 steel of various print orientations. Both API 5L X65 Wire and Powder printed samples were tested. The API 5L X65 Wire printed samples consisted of XY-0°, XY- 45° and XZ-90° orientations while the API 5L X65 Powder printed samples consisted of XZ- 45° and XZ-90° orientations. Through this Final Year Project, fatigue tests were done to determine the fatigue limits of various samples. Corresponding S-N (stress-life) curves were also plotted for further analysis of the fatigue properties of the samples. Fractographic examination was carried out using Scan Electron Microscopy, which showed a correlation between process induced defects and fatigue properties of the samples. In general, the fatigue properties of the samples can be improved by reducing the process induced defects. Tensile tests were conducted on the same materials by another fellow FYP student. As tensile test results are critical to the fatigue tests focused in this report, the tensile results were used and discussed along with the fatigue test results in this report.